Social Security Reform : Legal Analysis of Social Security Benefit Entitlement Issues. (U.S. Congressional Research., 2009)
Analyzes legal issues related to beneficiaries' entitlement to social security benefits, in light of social security reform proposals. Discusses Congressional authority to modify entitlements, Congressional guarantee of social security benefit payments, and legal issues involved in the payment of social security benefits from the social security trust fund in the event of insolvency.